Public opinion about social assistance in Sweden 1985 - Gustafsson, Björn; Aguilar, Renato (University of Gothenburg, 1994)
The questions about social assistance included opinions on how much money per month adults and children in different age groups needs, the level of assistance that should be given for each additional child as compared to the level of assistance attributed to the first child, and level of assistance compared to the level of old-age pension. The respondents were asked if they believed that their own family was entitled to social assistance, and what they would do if there would not be enough money for food and rent. Background variables included information on marital status, age, existence of children in the family, type of neighbourhood, education, labour force status, socio-economic status, and monthly disposable income.

I en enkätundersökning utförd av SCB ställdes bland annat ett antal frågor om socialbidragen i Sverige. Respondenten fick ange hur mycket man bör ha att leva på per månad, hur bidragen bör variera med familjestorlek och hur mycket en socialbidragstagare bör ha att leva på i jämförelse med en folkpensionär. Dessutom fick man göra en bedömning av om man trodde den egna familjen var berättigad till socialbidrag och vad man skulle göra om pengar till mat och hyra inte räckte. Ett antal bakgrundsfrågor berör civilstånd, hushållets storlek och ålderssammansättning, bostadsort, utbildning, eget och make/maka/samboendes förvärvsarbete samt hushållets månadsinkomst.
Allmänhetens åsikter om socialbidrag 1985
Keywords: Social welfare policy; Välfärdspolitik; Social Sciences; Samhällsvetenskap; Social Work; Socialt arbete